2018
DOI: 10.1111/aas.13227
|View full text |Cite
|
Sign up to set email alerts
|

Volatile anaesthetics and postoperative delirium in older surgical patients—A secondary analysis of prospective cohort studies

Abstract: Each VA may have different effects on postoperative cognition. Further studies using a prospective randomized approach will be necessary to discern whether anaesthetic type or management affects the occurrence of postoperative delirium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…We also screened two patients who inhaled volatile anesthetic. Some experimental studies [40] showed that volatile anesthetics may be induce cell injury and even promote neuro-pathogenesis, so volatile anesthetics were regarded as high risk factor for POD. On the contrary, others researches [41] demonstrated that volatile anesthetics take neuroprotective effect and do not provide any convincing data to verify their impact on POD.…”
Section: Discussionmentioning
confidence: 99%
“…We also screened two patients who inhaled volatile anesthetic. Some experimental studies [40] showed that volatile anesthetics may be induce cell injury and even promote neuro-pathogenesis, so volatile anesthetics were regarded as high risk factor for POD. On the contrary, others researches [41] demonstrated that volatile anesthetics take neuroprotective effect and do not provide any convincing data to verify their impact on POD.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative delirium is a prevalent complication that is frequently observed after surgery and general anesthesia ( Sieber et al, 2018 ; Kinjo et al, 2019 ). Generally, POD shows various symptoms, such as short-term memory impairment and anxiety ( Smith et al, 2016 ; Jin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Those who considered a cut-off to be reasonable used benzodiazepines rarely and preferably prescribe neuroleptics, opioids and alpha-agonists instead. Particularly promethazine was frequently used in the elderly, even though it has an extraordinary high anticholinergic burden (17,18), see table 6. The long-acting clorazepate was less frequently used in out-patient than in-patient anesthesia.…”
Section: Pharmacological Treatment Of Postoperative Delirium In the Pacumentioning
confidence: 99%
“…Already 10 min after PACU admission, a pathologic RASS or NuDeSc-Score, often described as emergence delirium (ED), was associated with later delirium on the ward (OR 2.4; 1.5–3.9 CI) and death after 3 months (OR 1.4; 0.7–3.4 CI) [ 5 ]. Immediately after awakening and extubation, Monk found a 3.7% incidence of ED, declining to 1.3% when re-evaluated in the PACU [ 6 ]. Another study found a 4% incidence of ED at the time of discharge from the PACU [ 7 ].…”
Section: Introductionmentioning
confidence: 99%